Physiological quality of parsley seeds in function of size - de Barros, Renato Téo [UNESP]; Martins, Cibele Chalita [UNESP]; Jeromini, Tatiane Sanches [UNESP]; da Silva, Givanildo Zildo; Filho, Arthur Bernardes Cecílio [UNESP] (Universidade Estadual de Londrina, 2021)
Parsley seeds are commercialized without classification by size during processing, unlike other crops. This classification procedure allows the standardization of seed size for high precision in sowing, disposal of unwanted material, and selection of high quality seeds. The aim of this study was to verify the effect of seed size on germination, vigor, and yield performance of two parsley cultivars. Seeds from eight lots of parsley of ‘Portuguesa’ and ‘Chacareira’ cultivar were separated into three size classes, represented by the seeds retained in the sieves of 0.84, 1.00 and 1.41mm mesh opening. After classification, seeds were evaluated in the laboratory for water content, germination percentage, first count, and thousand seed weight. In the field, the fresh and dry weight of aerial part and the final number of plants (stand) were evaluated after 78 days of sowing. The experimental design was the completely randomized design in an 8 x 3 factorial scheme (eight lots and three sieve opening) with four replicates, for both cultivars. Data obtained were subjected to analysis of variance and means were compared using Tukey test at 5% probability level. It was concluded that the parsley seeds separated by the 1.41 mm sieves showed higher vigor, and consequently, greater success in stand establishment at the field than those separated by other sieve size. The use of sieves in the classification of parsley seeds helps in obtaining lots with superior physiological quality.
Qualidade fisiológica de sementes de salsa em função do tamanho
Keywords: Germination; Petroselinum crispum (Mill.); Processing; Sifting; Vigor